Sustainable Cultivation Process of Family, School and Community to Enhance the Sufficiency Behavior of Children - Corriere, Chatchaya; Preededilok, Fuangarun (An Online Journal of Education, 2020)
In this study, the research objective is to analyze sustainable cultivation process of family, school and community to enhance the sufficiency behavior of children. The researcher interviewed 4 experts to acquire the data used in the study, which were collected, analyzed and summarized. In the context of child-rearing, cultivating refers to bringing up and developing the child to achieve good habits that are deep-seated. The process of cultivation refers to procedures used in the cultivation of sufficiency behavior, which comprise 4 steps: provoking thought, planning, action and evaluation. Additionally, the factors of sufficiency behavior cultivation process mentioned in this study are reinforcement, children’s knowledge and understanding, cultivator’s knowledge and understanding, the relationship between the cultivator and children, the understanding of the child nature, the individual difference behavior, being a good model, continuation of period, and supports. Conditions of sufficiency behavior cultivation process are the influence of social media consumption on behavior, not being open-minded to new things, child-rearing practices, and relationships between people in the community.